The Effect The Effect of Fiber Orientation on the Compressive Strength of Palm Fruit Fiber Composite Beams - Marsianus mario fredirikus hanmina; Yeremias M. Pell (Universitas Nusa Cendana, 2025)
The demand for wood for construction continues to increase, while the supply of quality wood is decreasing. Therefore, a new alternative is needed to replace wood, one of which is by utilizing palm fruit fiber as a basic material for making composite wood as a new material to replace wood. This study uses an experimental testing method where the composite beams that have been molded by hand lay-up press with polyester resin reinforced with palm fruit fiber that has been treated with 5% alkali for 2 hours, and a fiber volume fraction of 35%. The variations in fiber orientation tested include parallel and perpendicular fibers. The compressive strength test specimens were made according to the ASTM D695-02a standard and tested using a compressive strength testing machine. The test results showed that the composite beam with parallel fibers had the highest average compressive strength and tension, namely 13,851.72 MPa and 42.94 MPa, while the perpendicular fiber orientation produced the lowest value. The highest strain was obtained in the composite with parallel fiber orientation, namely 0.16. While the highest modulus of elasticity was obtained in the composite beam with perpendicular fiber orientation, namely 432.38.